Penerapan NodeMCU Terhadap Pemberitahuan Banjir dengan Menggunakan Metode GAMMU - Zulfahmi Syahputra; Muhammad Syahputra Novelan (Universitas Islam Sumatera Utara, 2020)
Disasters can come anytime and anywhere so that can not be predicted, flood disasters for example, at the level of water surface in the river is an important parameter in flood disasters therefore it is necessary to take measurements to detect flooding early. This research aims to create a prototype system for warnings before flooding. With the implementation of NodeMCU, Water Level and SMS Gateway with GAMMU method intergrated with arduino uno to measure water level. NodeMCU microcontroller as the sending media and sms receiver used to provide information about water level as well as ALERT, ALERT and ALERT alerts via SMS Gateway short message. The methods and procedures used are, Planning, Material Collection, Miniature System Creation, Hardware Design, and Creation of arduino-uno programs using NodeMCU. The results and discussion of the research obtained is that sensors can read water level and nodeMCU modules can transmit water level data information that has been read by sensors.